2012
DOI: 10.1159/000336649
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 Stimulates Small Artery VCAM-1 Expression through p38MAPK-Dependent Neutral Sphingomyelinase

Abstract: Endothelin-1 (ET-1) stimulates vascular cell adhesion molecule (VCAM-1) expression, a process associated with arterial remodelling. However, the pathways activated by ET-1 that lead to VCAM-1 expression are not fully understood. It is reported that sphingomyelinases are necessary for VCAM-1 expression in response to cytokines. Our aim was to investigate the role of sphingomyelinases in ET-1-induced VCAM-1 expression. Acid and neutral sphingomyelinase activities were measured in extracts from rat mesenteric sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 105 publications
1
13
0
Order By: Relevance
“…In this regard, it has been reported that ET-1 stimulates nSMase activity through a p38MAPK-dependent pathway, leading to vascular cell adhesion molecule (VCAM-1) expression (38). The activation of the BK-B 1 receptor leads to the activation of SMase, and the generated ceramide induces vasodilatation in rat mesenteric small arteries (25).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been reported that ET-1 stimulates nSMase activity through a p38MAPK-dependent pathway, leading to vascular cell adhesion molecule (VCAM-1) expression (38). The activation of the BK-B 1 receptor leads to the activation of SMase, and the generated ceramide induces vasodilatation in rat mesenteric small arteries (25).…”
Section: Discussionmentioning
confidence: 99%
“…In that context, the effect of the physiologic vasoconstrictors endothelin-1 (ET-1) on nSMase2 was studied. ET-1 activates nSMase2 to induce VCAM-1 expression in rat small mesenteric artery (Ohanian et al , 2012). Probing the system further, the effect of dietary Mg 2+ deficiency was studied.…”
Section: Nsmase2 As a Regulator Of Biological Functionsmentioning
confidence: 99%
“…Among the mechanisms possibly involved in the activation of nSMase2 by MMP2, we investigated the role of p38MAPK, which is early activated in response to agents such as TNF-α [18] or endothelin-1 [24] . Results presented in Fig.…”
Section: Resultsmentioning
confidence: 99%